Elevated chronic inflammatory factors and myeloid-derived suppressor cells indicate poor prognosis in advanced melanoma patients - Jiang, Huanhuan; Gebhardt, Christoffer; Schulze, Torsten; Utikal, Jochen; Umansky, Viktor (International journal of cancer, 2015)
Chronic inflammation is considered to be one of the hallmarks for tumor initiation and progression. Moreover, a long-term production and accumulation of inflammatory factors lead to a local and systemic immunosuppression associated with cancer progression. However, the correlation between inflammatory mediators, immunosuppressive cells and the clinical outcome of malignant melanoma patients was poorly investigated. In this study, we performed a complex analysis of various inflammatory factors, myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs) in the peripheral blood of patients suffering from malignant melanoma of different stages. We demonstrated that levels of serum IL-1β, IFN-γ and CXCL10 were significantly increased in advanced melanoma patients. In addition, these factors were found to be associated with an increased frequency of MDSCs and Tregs as compared to age- and gender-matched healthy donors. Importantly, advanced melanoma patients with signs of progression displayed markedly elevated concentrations of IL-1β and CXCL10 as compared to patients with stable disease. Moreover, an enrichment of circulating monocytic (Mo)-MDSCs significantly correlated with a decreased progression free survival of these patients. Our data highlight a complex association between circulating inflammatory mediators, Mo-MDSCs and the clinical outcome as well as suggest that their levels in patients with advanced melanoma are of important prognostic value allowing the identification of those with high risk of disease progression.
Gesehen am 05.12.2017